Reducing COVID-19 Mortality in Senegal through Community Case Management - Thiam, Sylla; Soumaré, Masserigne; Carter, Jane (PAMJ One Health, 2021)
Like many countries across the world, Senegal is facing a second wave of the COVID-19 pandemic with an increase in hospital admissions and deaths, putting pressure on an already overstretched health workforce. This situation requires new and innovative measures to reverse the trend and avoid overwhelming the health system. Community Case Management is a proven strategy in healthcare that could be a powerful tool in preventing severe cases and reducing deaths related to COVID-19. This proposed strategy is based on early detection of cases and home-based management by community health workers.
Copyright: Sylla Thiam et al. PAMJ - One Health (ISSN: 2707-2800). This is an Open Access article distributed under the terms of the Creative Commons Attribution International 4.0 License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Available online at: https://www.one-health.panafrican-med-journal.com/content/article/4/13/full
Keywords: COVID-19; Deaths; Community case management; Health workforce